Study on the Structuring of Music for Buddhist Folk Funeral Rituals in Bijie - Huang, Jun (International Journal of Social Sciences and Public Administration, 2024)
I think I have made an in-depth study of folk Buddhist funeral ceremony music in Bijie area, which aims to explore the origin, development, evolution of folk Buddhist funeral ceremony music in Bijie area, as well as its position and role in society and culture, and education. This study adopts a variety of research methods such as field survey, literature study, and music analysis. A large amount of musical materials were collected through field surveys and recordings of different folk Buddhist funeral ceremony music in the Bijie area. Relevant historical documents, folklore and oral history materials were also sorted out and analyzed to understand the historical origin and cultural background of funeral ceremony music. The results of the study show that the folk Buddhist funeral ceremony music in the Bijie area has a long history and a unique style. These musical compositions usually consist of elements such as Buddhist scriptures, mantras, Buddhist music and folk music, forming a unique musical form. In funeral ceremonies, these musical compositions are used to pay homage to the deceased, transcend the spirits of the dead, and protect the living, etc., and they have both religious ceremonial and social functions (ethics and morals, Buddhist education, and rituals). In addition, the study also found that folk Buddhist funeral ritual music in the Bijie area was influenced by a variety of factors during its evolution, such as regional culture, religious sects, and social change. With the development and change of society, the funeral ceremony music also evolved and innovated, gradually forming unique local characteristics. In general, the music of BiJie folk Buddhist funeral rituals is characterized by its solemnity, solemnity, sadness, and mourning, and adds a unique atmosphere to the funeral rituals through various forms of Buddhist scripture recitation, gatha and music performance, so that people are more able to feel the presentation of cultural phenomena such as memorialization and prayers for the deceased, and expectations and teachings for the living, and so on. It reveals the historical origin, cultural background and evolution process of the music of Bijie folk Buddhist funeral ceremony, and provides theoretical and practical guidance for the protection and inheritance of this unique music culture.